Evaluación de dosis de agentes clarificantes naturales en las características fisicoquímicas de la panela artesanal de la comunidad de Aguafría, Junín - Bravo Zamora, Beatriz María (2020)
The objective of this investigation was to determine the physicochemical characteristics of the artisan panela produced in the community of Agua Fria in Junín canton through the adequate use of natural clarifying agents. A two-factor AXB arrangement was used in a completely randomized design (DCA) with three replicates for each treatment, taking 25 L of sugarcane juice for each replicate as the experimental unit. For this, the following factors were manipulated. A: types of natural clarifying agents and B: doses of natural clarifying agents expressed in ml / L (100 ml, 130 ml and 160 ml / 25 L). The following variables were evaluated: color and suspended solids in artisan panela. The dose that allowed obtaining the best physicochemical characteristics in artisan panela was level b3 (160 ml). The treatment with the lowest amount of suspended solids was T6 (macerated solution of mature yellow cocoa pod, characteristic of the national variety 160 ml / 25 L of sugarcane juice) with a value of 0.1 g / 100 g of panela and for the color variable the T3 (macerated solution of the stem bark in the state of intermediate maturity of the white bur 160 ml / 25 L of sugar cane juice) with a value of 57 absorbance with a wavelength of 560 nm. It is important to mention that this study allowed to improve the color of the panela and reduce the solids in suspension.